2020
DOI: 10.1021/acs.jpclett.0c02347
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Field Manipulation of Naturally Occurring Microbial Chiral Peptides to Regulate Gas-Hydrate Formation

Abstract: Clathrate hydrates are non-stoichiometric crystalline inclusion compounds, wherein a water host lattice entraps small guest molecules in cavities, with methane hydrates the most widespread in Nature. Recent studies have shown that proteins and polypeptides produced by micro-organisms can accelerate methane-hydrate formation. However, the role of magnetic fields and chirality in such phenomena is heretofore unclear. Here, we find primafacie evidence of differently-oriented magnetic fields of varying strength sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
(97 reference statements)
1
2
0
Order By: Relevance
“…In the presence and absence of an electric field, release and uptake of sII neon hydrate showed that activation energies for uptake and release of neon in the absence of an electric field were 14.9 and 16.4 kJ/mol which indicated a good agreement with the experimental measurements, however, the release value in the existence of an electric field was declined to 6.5 kJ/mol [299]. By simulating the role of the magnetic field on the formation of CH4 hydrate in the existence of micro-organisms (proteins), some evidence of oriented magnetic fields on the hydrateformation kinetics by a prototypical aromatic peptide was confirmed [300]. Based on exploring the dissociation of N2 hydrate within SWCNT and under the axial electric field, the electric field was found to change the orientations of water dipoles which results in altering the diffusion coefficient and hydrogen-bonding network of the water molecules [301].…”
Section: Hydrate Stability and Dissociationsupporting
confidence: 74%
“…In the presence and absence of an electric field, release and uptake of sII neon hydrate showed that activation energies for uptake and release of neon in the absence of an electric field were 14.9 and 16.4 kJ/mol which indicated a good agreement with the experimental measurements, however, the release value in the existence of an electric field was declined to 6.5 kJ/mol [299]. By simulating the role of the magnetic field on the formation of CH4 hydrate in the existence of micro-organisms (proteins), some evidence of oriented magnetic fields on the hydrateformation kinetics by a prototypical aromatic peptide was confirmed [300]. Based on exploring the dissociation of N2 hydrate within SWCNT and under the axial electric field, the electric field was found to change the orientations of water dipoles which results in altering the diffusion coefficient and hydrogen-bonding network of the water molecules [301].…”
Section: Hydrate Stability and Dissociationsupporting
confidence: 74%
“…The experimental apparatus for hydrate-formation included gas cylinders, a 316 stainless steel pressure vessel with approximately 340 cm 3 , refrigerator to control the temperature of the vessel, tilting shaker to agitate the water inside the vessel and logging system to record the data during the formation time (Figure 2). Detailed information about the hydrate system is presented in our previous work [26]. Before each experiment, the vessel was sterilised using an ethanol solution (70 wt%).…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Similarly, for biological surfaces (proteins and particularly favorable peptide sequences), Ghaani and co-workers have studied with acuity, using both experimental and molecular-simulation approaches, the interplay of hydrophobic and hydrophilic amino-acid residue sequences for methane-hydrate formation thereon, including the effect of chirality and magnetic fields. 111–113 It was found, broadly, that judicious selection of alternating hydrophobic/hydrophilic surfaces allows for the optimal “scaffolding” to promote methane-hydrate formation, and general establishment of “molecular-surface engineering” design principles and rules is of course important if one wishes to regulate and manipulate surface-based hydrate formation (whether inhibition or promotion, although the present review focuses, naturally, on inhibition).…”
Section: Anti-hydrate Nucleation Surfacesmentioning
confidence: 99%